2017
DOI: 10.4236/as.2017.88055
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Natural and Synthetic Fungicides on the Pink Root Disease of Onion (<i>Allium cepa </i>L.), in Nursery

Abstract: Onion is an important vegetable in Senegal horticulture, where it occupies the first place. However in the greatest areas production like the Gandiolais, in the North of Senegal, Pink root disease caused by a soil born fungus Pyrenochaeta terrestris (Hansen) Gorentz, Walker and Larson affects its productivity especially in nursery. On soil sterilized and inoculated by the fungus, we tested 5 natural fungicides and 2 synthetic fungicides, to measure their effectiveness on the Pink root disease on onion, in nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Translaminar fungicides help in even distribution of fungicides from the upper parts of the plants to the lower parts [36]. Synthetic fungicides such as azoxystrobin, prochloraz, or thirame are mostly employed in crop protection, while examples of natural fungicides include rosemary oil, tea tree oil, and jojoba oil among many others [37][38][39].…”
Section: Fungicidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Translaminar fungicides help in even distribution of fungicides from the upper parts of the plants to the lower parts [36]. Synthetic fungicides such as azoxystrobin, prochloraz, or thirame are mostly employed in crop protection, while examples of natural fungicides include rosemary oil, tea tree oil, and jojoba oil among many others [37][38][39].…”
Section: Fungicidesmentioning
confidence: 99%
“…include Azadirachta indica leaf extract [97], peels of Ipomoea batatas Lam [98], Curcuma longa leaves [37], C. papaya leaves [38], and thyme and lemongrass extract [99].…”
Section: Natural Products As Fungicides Several Plant Extracts Have Been Successfully Employed As Fungicides Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that some plants produced secondary metabolites, such as essential oils and volatile compounds that can have a biocidal action against postharvest pathogens [49,50]. Commercial products of natural fungicides such as rosemary oil, neem oil, Aloe vera gel (AVG), tea tree oil and jojoba oil, among many others, are now used in crop protection and preservation as fungicides [51][52][53], while commercial natural insecticides include nicotine and pyrethrum, amongst others [54,55]. Medicinal plant extracts could be a useful alternative to synthetic fungicides in the control of rot fungi when handling fruits and vegetables after harvest.…”
Section: Introductionmentioning
confidence: 99%